2001
DOI: 10.1046/j.1365-2567.2001.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cellular immunity to lymphocytic choriomeningitis virus is independent of CD1d1 expression

Abstract: SUMMARYCD1 molecules are cell surface glycoproteins, structurally similar to major histocompatibility complex (MHC) class I molecules. The murine CD1d1 molecule has been shown to be essential for the positive selection of a unique subpopulation of T cells [the natural killer (NK) T cells], as CD1d1-de®cient mice lack NK T cells. These cells have recently been suggested to play an important role in the induction of innate immunity (i.e. NK cells) and the regulation of immune homeostasis. As such, it was asked w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 60 publications
1
25
1
Order By: Relevance
“…Others have also seen such a reduction in liver NKT cells following treatment of mice with ␣-GalCer (19,43,48) or anti-CD3 (18) and have reported a role for NKT-cell-produced IFN-␥ in the induction of NK cell activity (13,19). In the case of LCMV, we have found that the virus-induced NK cell activity is actually normal in an NKT-cell-deficient environment (i.e., CD1d1-deficient mice) (57), and LCMV infection also resulted in the loss of NKT cells in IFN-␥-deficient mice (Table 1). This suggests that the importance of NKT cells in various infections will be dependent not only on the pathogens, but also the cytokines that they induce.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Others have also seen such a reduction in liver NKT cells following treatment of mice with ␣-GalCer (19,43,48) or anti-CD3 (18) and have reported a role for NKT-cell-produced IFN-␥ in the induction of NK cell activity (13,19). In the case of LCMV, we have found that the virus-induced NK cell activity is actually normal in an NKT-cell-deficient environment (i.e., CD1d1-deficient mice) (57), and LCMV infection also resulted in the loss of NKT cells in IFN-␥-deficient mice (Table 1). This suggests that the importance of NKT cells in various infections will be dependent not only on the pathogens, but also the cytokines that they induce.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, viral clearance has multiple mechanisms by which it can occur and is different depending upon the virus. We have found that even in an NKT-cell-deficient (i.e., CD1d1 knockout mice) environment, the in vivo control of LCMV is comparable to that in wild-type mice (57). Thus, in that model, either the lack of NKT cells is beneficial, by preventing an NKT-cell-mediated cytotoxic response affecting hepatocytes and other tissues, or, alternatively, NKT cells simply play no role in the control of that virus infection.…”
Section: Discussionmentioning
confidence: 90%
“…Regardless to the effect of LCMV on iNKT cells, these cells do not seem to be indispensable for innate and CTL responses in the spleen, as Cd1d À/À and WT mice have similar splenic viral loads and LCMV-specific cytotoxic T-cell responses [42]. However, the same team later reported that LCMV infection of Cd1d À/À mice resulted in significantly higher splenocyte production of IL-2, IL-4 and IFN-g than in WT controls [43].…”
Section: Lymphocytic Choriomeningitis Virus (Lcmv)mentioning
confidence: 99%
“…Mouse H-2D b tetramers loaded with GP33 and NP366 [14] and conjugated with PE were kindly provided by Dr. Liisa Selin (University of Massachusetts Medical School, Worcester, MA). The labeling procedure and FACS analyses were performed as described previously [28,29]. Samples were analyzed on a FACSCalibur flow cytometer (Becton Dickinson, Mountain View, CA), with 10,000-50,000 events acquired per sample as indicated.…”
Section: Antibodies and Facs Analysismentioning
confidence: 99%